Grite, grite outra vez! – um estudo de caso sobre o Star System e Vincent Price - Gamba, Janaina dos Santos (Universidade do Vale do Rio dos Sinos, 2011)
The main objective of this article is to provide a brief overview of the career of the actor Vincent Price, which existed simultaneously with cinema's Golden Age of Horror. The article traces a parallel between the beginning of horror as a genre, its development and unfolding in the film industry, as well as the connection with Vincent Price, one of the best known actors in his genre, the Star System and archetype construction. Using as methodological and theorical base, are consulted many works, such as: Horror: The Reader of Marc Jancovich, O Gênio do Sistema of Thomas Schatz, As Estrelas de Cinema of Edgar Morin, Vincent Price: A Daughter’s Biography of Victoria Price, besides other books, publications and movies of the most diverse directors starred by Vincent Price. Will be examinated some of the main features of his career as well the films he starred, in a way to investigate why his images is so attached to horror films, despite the flaws that the Star System had to build it.
Keywords: Cinema; Horror; Vincent Price; Star System; Arquétipo; Archetype